PENGUJIAN COGNITIVE WALKTHROUGH ANTARMUKA PERPUSTAKAAN DIGITAL (E-LIBRARY) PUSAT DOKUMENTASI DAN INFORMASI ILMIAH – LIPI (PDII-LIPI) - Maryati, Ira; Ardiansyah, Firman; Kusuma, Wisnu (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2014)
Interface design has a significant role towards the successful of digital librarys application use. Digital libraryservices developed by Centre for Scientific Documentation and Information - Indonesian Institute of Sciences (PDII-LIPI) has yet to be evaluated. This research analyzed the design of the web interface of PDII-LIPI’s digitallibraries using the method of cognitive walkthrough (CW). The aim of the research is to identify user constraints inusing PDII-LIPI’s digital libraries. Object of this study are three menus in digital library web interface that is “KaryaIlmiah Indonesia”, “Buku Elektronik”, and “Jurnal Indonesia (ISJD)”. CW testing parameters for PDII-LIPI’s digitallibrary interface consists of the successful completion of the task, and the effectiveness of the task. The successfulcompletion of the task was assessed by comparing the standard time with task completion time by respondents. Effectiveness accessed based on the processing time of each stage and the number of mistakes made by therespondent. The test results showed that all respondents successfully completed the task with the time that goesbeyond the standard set time. The analysis was conducted on all test results indicate that the obstacles faced byusers in general are finding menu of “E-Library”, specify the search facility is used, and searching the articles.